Utilizing Current Resources to Deliver Sustainable Living Solutions in Refugee Camps. Case study: Al Za’atari Camp - AL ZAHABI, SALMA (2022)
-Purpose: Due to the tremendous negative impacts caused by man-made disasters on human living worldwide, study emphasize on finding sustainable solutions for stable and durable living in refugees camps by looking into longer period occupancy using existing available resources and reducing footprints caused by poor refugee camps early planning, infrastructure, and management. -Aims & Objectives: Study focus on developing existing facilities by looking into resources and potentials available within camp borders and producing affordable, self-sufficient, and modular designs accessible and durable for longer living. This paper will be based on selected case study “Al Za’atari Camp” for Syrian refugees in northern Jordan; recorded as the second largest refugee camp in the world. Study objective offer camp management proposal as a sample for other refugee’s camp to upgrade current system and experience better living standards until refugees return back home, and utilize camp facilities using for future usages as a second occupancy phase. -Design/Methodology/Approach: Based on an extensive literature review undertaken to compare current project conditions and available shelter solutions, study surveys Al Za’atari Camp UNHCR Management and looks into camp currents activities, monthly reports, and factsheets, proposing flexible design solutions and strategies that are examined using design approach and simulation analysis based on detected issues and problems. -Finding/Outcomes: The study results in proposing five sustainable approaches through Education & Training, Livelihoods & Camp Management, Shelter Planning, Power Generation, WASH, and Waste Management facilities on a selected district and examining approaches that are able to ensure basic healthy environment and modular shelter solutions for refugees based on the area requirements and usage.